1980
DOI: 10.1901/jeab.1980.33-119
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Temporal Location of Polydipsic Licking in the Rat

Abstract: We studied the variables controlling the temporal location of polydipsic licking. Four rats were trained on a mixed fixed-ratio 10 (no tone) chained fixed-ratio 10 (no tone) fixed-ratio 90 (tone) schedule and on a multiple fixed-ratio 10 (tone) fixed ratio 100 (no tone) schedule. On the multiple schedule, drinking followed pellets if a fixed ratio 100 was upcoming for all four subjects and for two of the subjects if a fixed ratio 10 was upcoming. On the mixed schedule, drinking preceded the fixed-ratio 90 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In Experiment 1, we confirmed that omission of food substantially reduces both the probability and the bout duration of drinking, but found that omission had relatively little effect on the probability of induced wood-chewing and no significant effect on its bout duration. The fact that induced drinking is reduced, but not eliminated, by omission of food suggests that both the eliciting and the discriminative properties of food presentation contribute to the maintenance of SIP (see also Alferink, Bartness, &Harder, 1980, andHeyman &Bouzas, 1980, for a similar conclusion). One approach to explaining the differences between induced chewing, drinking, and aggression might therefore be to postulate differences in the relative contribution of eliciting and discriminative factors.…”
Section: Subjects and Apparatusmentioning
confidence: 95%
“…In Experiment 1, we confirmed that omission of food substantially reduces both the probability and the bout duration of drinking, but found that omission had relatively little effect on the probability of induced wood-chewing and no significant effect on its bout duration. The fact that induced drinking is reduced, but not eliminated, by omission of food suggests that both the eliciting and the discriminative properties of food presentation contribute to the maintenance of SIP (see also Alferink, Bartness, &Harder, 1980, andHeyman &Bouzas, 1980, for a similar conclusion). One approach to explaining the differences between induced chewing, drinking, and aggression might therefore be to postulate differences in the relative contribution of eliciting and discriminative factors.…”
Section: Subjects and Apparatusmentioning
confidence: 95%
“…What then of results showing that drinking occurs less reliably after nonfood stimuli, even if they have exactly the same predictive significance as food (e.g., Alferink et al, 1980;Allen & Porter, 1977;Rosenblith, 1970)? The answer may lie simply in the poorer (temporal) discriminative control exerted by nonfood stimuli (cf.…”
Section: Subjectsmentioning
confidence: 97%
“…The latter outcome probably is responsible for the absence of stimulus-induced drinking in several studies because postpellet licking was established before exposure to S-(e.g., Dougan et al, 1985;Iversen, 1977;Jacquet, 1972;Porter et al, 1975;Rosenblith, 1970). In contrast, in all successful demonstrations of stimulus-induced drinking (Alferink et al, 1980;Corfield-Sumner et al, 1977;Minor & Coulter, 1982) Swas introduced before stable interim responding had developed.…”
Section: Stimulus-induced Drinkingmentioning
confidence: 99%
“…Even though the brief stimuli lacked consummatory properties, drinking occurred after both events. Stimulus-induced drinking also occurred when a fixed-ratio 10 (FR 10) schedule alternated randomly with a chained FR 10 FR 90 schedule (Alferink, Bartness, & Harder, 1980). In this procedure, completion of 10 responses occasionally produced a stimulus that accompanied a long interval to reinforcement (i.e., the FR 90 link of the chain).…”
mentioning
confidence: 99%
See 1 more Smart Citation